Mental Health States of Housewives: an Evaluation in Terms of Self-perception and Codependency. - Kaplan, Veysel (International Journal of Mental Health & Addiction, 2023)
Housewives are individuals who assume the role of caregiver in the family in almost every society and experience serious psychological difficulties in line with this role. These psychological difficulties may develop due to the pathological relationships that women have, especially with their family members. In this context, the study aims to examine the mental health states of housewives within the framework of codependence and self-perceptions. This study, which was planned as descriptive, relational, and cross-sectional, by online questionnaire method, consists of 371 housewives. Personal information form, Codependency Assessment Tool (CODAT), social comparison scale (SCS), and the Symptom Checklist-90-Revised (SCL-90-R) were used to collect data. In the analysis of the research, a structural equation model was established by using SPSS 25 and AMOS 23 package programs. It was found that the mean age of the housewives included in the study was 35.19 ± 9.85 and 35.5% of the participants were university graduates, 13.2% lived in an extended family, 13.7% had a poor relationship with their spouse, and 51.5% were only responsible for housework. Besides, according to the results of the study, it was found that the total mean score of SCS was 75.16 ± 21.73, SCL-90-R was 1.96 ± 0.95, and CODAT was 76.16 ± 17.75. In the case of analysis, there was strong correlation between the mental status of housewives and both their codependency levels and their self-perceptions. It has been determined that increased levels of codependency and negative self-perception of housewives increase the psychological symptoms experienced.